Proposing Blue Sukuk in Indonesia: An Interpretive Structural Model - Aam Slamet Rusydiana; Mohammad Iqbal Irfany (Shirkah: Journal of Economics and Business, 2021)
This research aims to identify the priority factors that being barriers to issue and develop Islamic blue sukuk in Indonesia. Employing the Interpretive Structural Modeling (ISM) method, it also offers several solutions for the identified problems. As an advanced planning methodology, ISM is used to identify, analyze, and summarize various relationships among factors that define a problem, model, or issue. In the ISM framework, there are three criteria of blue sukuk development in Indonesia including (1) aspect or foundation required within the framework of developing blue sukuk; (2) infrastructure that will be used as a basis for sukuk issuance (underlying projects); and (3) stakeholders involved in the development of blue sukuk in Indonesia. Results show that important foundations needed in the development of blue sukuk are regulatory aspects, feasible underlying projects, investors, and inter-institutional coordination, respectively. Finally, possible underlying infrastructures for the issuance of Blue Sukuk are the development of integrated fishing villages as well as the procurement of large and environmentally friendly fishing boats.